STUDI LOGAM BERAT TEMBAGA, TIMBAL, KROMIUM, KADMIUM DAN SENG PADA AKAR MANGROVE RHIZOPHORA APICULATA DI DESA BAGAN ASAHAN BARU KECAMATAN TANJUNG BALAI KABUPATEN ASAHAN PROVINSI SUMATERA UTARA - Rafindo Sanjaya Saragih; Ria Retno Dewi Sartika Manik; Daniel Tony Edyt Siburian (Journal of Research and Publication Innovation, 2025)
Mangrove ecosystems are forests that grow in tidal areas, especially on protected beaches and river estuaries that are flooded at high tide and free from puddles at low tide and whose plant communities are tolerant of heavy metals. Heavy metals concentrations in marine sediments have been widely used to assess longterm anthropogenic inputs into the marine environment. Mangrove ecosystems have the ability to store heavy metals such us iron, manganese, Cr, Cu, Co, Ni, Pb, Zinc and Cd, which is known as biosorption. This type of mangrove (Rhizopora Apiculata) is one of several mangrove species that can absorb heavy metals. They do this througha dilution process, which dilutes the concentration of heavy metals in their body tissues, which reduces the metal’s toxicity. The aim of this research is to determine the levels of heavy metals in Rhizopora Apiculata mangrove roots based on the parameters copper (Cu), Lead (Pb), Chromium (Cr), Cadmium (Cd) and zink in Bagan Asahan Baru Village, Tanjung Balai. The results of the analysis of test data for the levels of heavy metals Copper, Lead, Chromium, Cadmium and Zink that were obtained were then compared with the water quality standarts that have been determine in Appendix IV PPRI Number 22 of 2021 concerning water quality standarts and the like. The results of heavy metal measurements on copper (Cu), Lead (Pb), Chromium (Cr), Cadmium (Cd) and Zink carried out in the Baristand Medan Laboratory, it can be concluded that the heavy metal concent in the roots of Rhizopora Apiculata Mangroves in the waters of Bagan Asahan Village Baru does not meet the quality standarts of PPRI No. 22 of 2021 class IV.